STRATEGI PENGEMBANGAN BISNIS KERIPIK BAYAM - Rusli M Rukka; Nurbaya Busthanul; Nur Fatonny (Jurnal Sosial Ekonomi Pertanian, 2018)
AbstractThe aim of this research is to understand the description of Business model canvas and to create a design of business transformation. The reseach held at CV. OAG Makassar, It is one of a company that produced spinach chips. In order to complete a valid data, researcher were conducted a participatory action reseach method, where the researcher also involved for more than two months in the company.  The general description of the company was explained in descriptive by describing the company resources position and their performance. Business model and its business transformation model were analized using business model canvas approach and customer emphaty map. The development strategy result of CV AOG business transformation is to improving the preserves of customer segment and so as their resource key. The improvement on value propositions like customer customization services, websites and social media in its value on channels and customer relationship produce a revenue streams from new product selling which made from spinach and other veggies. Improvement also needed in social activities on key activities, increasing partners such as event organizer and delivery services as key partners, also cost added for customization and social activity on cost structure.  Keywords : development strategy; bussiness model canvas;  spinach chips.